2011
DOI: 10.1021/jo201429w
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Addition of Malonates to Enones Catalyzed by a Primary β-Amino Acid and Its Lithium Salt

Abstract: Highly enantioselective Michael addition of malonates to enones was achieved using a mixed catalyst consisting of a primary β-amino acid, O-TBDPS (S)-β-homoserine, and its lithium salt. Various cyclic and acyclic enones were converted into 1,5-ketoesters in high yields (up to 92%) with high enantioselectivity (up to 97% ee) under mild reaction conditions. Details of synthesis of the catalyst, optimization of the reaction conditions for the Michael addition reaction, and a plausible reaction mechanism are descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Because of the presence of the acidic proton in the b-ketoester moiety, Michael adduct 4 aa was obtained as a 1:1 mixture of diastereomers, (2R)-and (2S)-3-oxo-2-[(R)-3-oxocyclohexyl]-3-phenylpropanoic acid ethyl ester, each with the same ee value. As was the case in our previous work of the Michael addition reaction of malonates to enones, [5] a mixed solvent system that consisted of an highly polar aprotic solvent and a haloalkane gave better results in terms of chemical and optical yields than did a simple solvent system ( Table 1, entries [13][14][15][16][17][18][19][20]. By carefully adjusting the solvent systems that consisted of DMSO or DMF with either CH 2 Cl 2 or CHCl 3 , we found that a 3:2 mixture of DMSO/CH 2 Cl 2 was the appropriate mixed solvent for further investigations (Table 1, entry 19).…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Because of the presence of the acidic proton in the b-ketoester moiety, Michael adduct 4 aa was obtained as a 1:1 mixture of diastereomers, (2R)-and (2S)-3-oxo-2-[(R)-3-oxocyclohexyl]-3-phenylpropanoic acid ethyl ester, each with the same ee value. As was the case in our previous work of the Michael addition reaction of malonates to enones, [5] a mixed solvent system that consisted of an highly polar aprotic solvent and a haloalkane gave better results in terms of chemical and optical yields than did a simple solvent system ( Table 1, entries [13][14][15][16][17][18][19][20]. By carefully adjusting the solvent systems that consisted of DMSO or DMF with either CH 2 Cl 2 or CHCl 3 , we found that a 3:2 mixture of DMSO/CH 2 Cl 2 was the appropriate mixed solvent for further investigations (Table 1, entry 19).…”
Section: Resultssupporting
confidence: 56%
“…Without any additives, this reaction afforded 4 aa in 82 % yield with 85 % ee (Table 2, entry 1). In our previous study of the Michael addition of malonates to enones, the addition of a catalytic amount of acid greatly improved the yield of the Michael adduct, [5] whereas the addition of a base would en-hance the generation of the enolate of 2 a. Although the addition of a catalytic amount of acid or base did not greatly affect the yield and enantioselectivity of 4 aa, the addition of water improved both of these results ( Table 2, entries 2-6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations